To fill the table using the function rule y = 29 - 3x, we need to substitute different values of x and solve for y.
Let's start by substituting x = 0:
y = 29 - 3(0) = 29 - 0 = 29
Now, let's substitute x = 1:
y = 29 - 3(1) = 29 - 3 = 26
Continuing with x = 2:
y = 29 - 3(2) = 29 - 6 = 23
For x = 3:
y = 29 - 3(3) = 29 - 9 = 20
And for x = 4:
y = 29 - 3(4) = 29 - 12 = 17
Finally, substituting x = 5:
y = 29 - 3(5) = 29 - 15 = 14
The completed table is:
| x | y |
|-------|-------|
| 0 | 29 |
| 1 | 26 |
| 2 | 23 |
| 3 | 20 |
| 4 | 17 |
| 5 | 14 |
fill the table using this function rule y=29-3x
1 answer